Cardiovascular adaptations to endurance training and detraining in young and older athletes - Giada, F.; Bertaglia, E.; de Piccoli, B.; Franceschi, M.; Sartori, F.; Raviele, A.; Pascotto, P. (International Journal of Cardiology, 1998)
In order to evaluate the influence of aging on cardiovascular adaptations to endurance training and detraining, 12 young (range 19-25 years) and 12 older (range 50-65 years) male cyclists were examined during the training and after 2 months of detraining. Twelve young and 12 older healthy sedentary males matched for age and body surface area were used as control groups. Each subject underwent a maximal exercise test using a cycle-ergometer in order to measure maximum oxygen consumption, an M-mode and 2D echocardiography in order to assess left ventricle morphology and systolic function, and a Doppler echocardiography for evaluating the diastolic filling pattern. During the training period both groups of athletes showed higher values of maximum oxygen consumption, left ventricular wall thicknesses, end-diastolic diameter and volume, as well as left ventricular mass, than their control subjects; in the older subjects the adaptation of the heart to aerobic training seems to be obtained mainly through a higher increase in left ventricular diastolic filling. In both groups no significant modifications in the ejection fraction and diastolic function parameters were recorded. After the detraining period the wall thicknesses decreased only in young athletes, while left ventricular mass and end-diastolic diameter and volume reduced only in older athletes. In conclusion, training and detraining induced nearly similar left ventricular morphological modifications in the two age groups, even though greater in the older athletes with respect to the ventricular mass and volume. No relevant differences were observed in the Doppler filling pattern between athletes and sedentary controls.